(untitled) (University Heart Journal, 2009)
Physical exercise is found to have positive health and well being of a person since time immemorial. Regular exercise has proved to normalize the elevated blood pressure of mild to moderate intensity by many studies. The blood pressure response to such exercise may also be used to screen normotensive persons for the risk of developing elevated blood pressure. For mild hypertension aerobic exercise and life style changes such as weight loss, dietary changes such as salt restriction and cessation of smoking are probably better choices. In moderate to severe essential hypertension, exercise should be combined with life style changes and medication. The aim of this review study is to delineate the effect of exercise in the control of elevated blood pressure. Methods used were analysis of the published article collected from the internet and other sources. The specific aims were to emphasis the importance of exercise as therapeutic intervention for the control of hypertension. doi: 10.3329/uhj.v5i1.3440 University Heart Journal Vol. 5, No. 1, January 2009 36-39